2014
DOI: 10.1021/jo4024914
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible Sortase A-Mediated Ligation Driven by Diketopiperazine Formation

Abstract: Sortase A (SrtA)-mediated ligation has emerged as an attractive tool in bioorganic chemistry attributing to the remarkable specificity of the ligation reaction and the physiological reaction conditions. However, the reversible nature of this reaction limits the efficiency of the ligation reaction and has become a significant constraint to its more widespread use. We report herein a novel set of SrtA substrates (LPETGG-isoacyl-Ser and LPETGG-isoacyl-Hse) that can be irreversibly ligated to N-terminal Gly-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 21 publications
0
38
0
Order By: Relevance
“…Wiliamson et al reported the synthesis of a depsipeptide that releases a relatively unreactive hydroxyacetyl moiety instead of a nucleophilic aminoglycine [40, 41• 42]. A second depsipeptide was synthesized by Liu and coworkers that involves release of a fragment that spontaneously deactivates via diketopiperazine formation [43]. These systems, which are best suited for N-terminal labeling, give excellent ligation yields with a variety of protein and peptide targets using only 1.0–3.0 equivalents of depsipeptide acyl donor.…”
Section: Driving Ligation Product Formationmentioning
confidence: 99%
“…Wiliamson et al reported the synthesis of a depsipeptide that releases a relatively unreactive hydroxyacetyl moiety instead of a nucleophilic aminoglycine [40, 41• 42]. A second depsipeptide was synthesized by Liu and coworkers that involves release of a fragment that spontaneously deactivates via diketopiperazine formation [43]. These systems, which are best suited for N-terminal labeling, give excellent ligation yields with a variety of protein and peptide targets using only 1.0–3.0 equivalents of depsipeptide acyl donor.…”
Section: Driving Ligation Product Formationmentioning
confidence: 99%
“…Therefore, we explored next whether MPI-SrtA could be used to modify proteins. In this case, bovine insulin was used as the model protein, as there is a glycine residue located at its N-terminus that has been established as a nucleophile in SML 56 . Bz-LPETGGS was used as the peptide donor as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of reaction reversibility, a handful of strategies have been introduced that drive reaction equilibrium through selective removal or deactivation of transpeptidation products. These strategies may be as simple as running the reaction under dialysis conditions to separate out low-molecular-weight byproducts (Kobashigawa, Kumeta, Ogura, & Inagaki, 2009; Refaei et al, 2011; Pritz et al, 2007), but also include the use of β-hairpins (Yamamura, Hirakawa, Yamaguchi, & Nagamune, 2011), depsipeptides (Liu, Luo, Flora, & Mezo, 2014; Williamson, Fascione, Webb, & Turnbull, 2012), or masked metal-binding peptides (Row et al, 2015) that prevent certain transpeptidation products from re-entering the catalytic cycle. Finally, advances have been made in expanding the substrate scope of sortase-catalyzed transpeptidations beyond the LPXTG motif.…”
Section: Commentarymentioning
confidence: 99%